Analysis of Proportion Calculation for Domestic Product in Modern Retail Indonesia - Wicaksena, Bagus; Utama, Riffa (UI Scholars Hub, 2018)
The increasing market for retail industry in Indonesia faces a challenge poses by sellers’ preference towards the selling of domestic goods. In order to overcome this problem, the government issues a mandate for retailer to sell domestic products as high as 80% of their traded goods. This may raise ineffectiveness in terms of the implementation since the capabilities in stock management varies among retailers, added with the absence of clear technical guidance that determines the fulfilment of 80% domestic product to be traded by a retailer. As such, there is a need to provide case-based recommendations addressing the governance and technical specification of the mandate to be applied. This study is aimed at formulating guideline to fulfil calculation requirements and providing policy recommendation for policy adoption by retailers. The study is done in 2016, whereby data collection is performed through interviews and focus group discussions with relevant parties representing 15 modern retailers. Analysis is done by carrying out stock keeping unit analysis in modern retailer and triangulate preliminary results through focus group discussion with key persons. The analysis shows that stock keeping unit management in modern retail must be integrated with a unique code that identifies the manufacturer origin which is issued by global standardization and distribution institution. In addition, the proposed system needs to be supported with policy of International unique code registration process, both by manufacturer and modern retail. In keeping with the refinement of relevant policy, there is also a need to have coordination amongst responsible authorities.